Health Belief Model and Labelling Theory in the Analysis of Preventive Behaviors to Address Biopsychosocial Impacts of Sexual Violence among Street Children in Yogyakarta - Khalifah, Intan Noor; Demartoto, Argyo; Salimo, Harsono (Journal of Maternal and Child Health, 2017)
Background: Street children are at high risk of sexual violence. Necessary measures should be undertaken to address deleterious biopsychosocial impacts of sexual violence. This study aimed to analyze the preventive behaviors to address biopsychosocial impacts of sexual violence among street children in Yogyakarta using Health Belief Model and Labelling Theory. Subjects and Method: This study was qualitative descriptive with phenomenology approach. The key informants for this study included Head of Rumah Impian Indonesia Foundation (a social non-government organization) and Director of PKBI, Yogyakarta. The main informants were the street children with assistance from Rumah Impian Indonesia Foundation. Supporting informants were health personnels of Jetis community health center and the street children